Multicentric randomised study of Helicobacter pylori eradication and pepsinogen testing for prevention of gastric cancer mortality: the GISTAR study. Issue 8 (11th August 2017) - Leja, Marcis; Park, Jin Young; Murillo, Raul; Liepniece-Karele, Inta; Isajevs, Sergejs; Kikuste, Ilze; Rudzite, Dace; Krike, Petra; Parshutin, Sergei; Polaka, Inese; Kirsners, Arnis; Santare, Daiga; et al.
Abstract : Introduction: Population-based eradication of Helicobacter pylori has been suggested to be cost-effective and is recommended by international guidelines. However, the potential adverse effects of widespread antibiotic use that this would entail have not been sufficiently studied. An alternative way to decrease gastric cancer mortality is by non-invasive search for precancerous lesions, in particular gastric atrophy; pepsinogen tests are the best currently available alternative. The primary objective of GISTAR is to determine whether H pylori eradication combined with pepsinogen testing reduces mortality from gastric cancer among 40–64-year-old individuals. The secondary objectives include evaluation of H pylori eradication effectiveness in gastric cancer prevention in patients with precancerous lesions and evaluation of the potential adverse events, including effects on microbiome. Methods and analysis: Individuals are recruited from general population (50% men) in areas with high gastric cancer risk in Europe and undergo detailed lifestyle and medical history questionnaire before being randomly allocated to intervention or control groups. The intervention group undergoes H pylori testing and is offered eradication therapy if positive; in addition, pepsinogen levels are detected in plasma and those with decreased levels are referred for upper endoscopy. All participants are offered faecal occult blood testing as an incentive for study participation. Effectiveness of eradication and the spectrum of adverse events are evaluated in study subpopulations. A 35% difference in gastric cancer mortality between the groups is expected to be detectable at 90% power after 15 years if 30 000 individuals are recruited. Biological materials are biobanked for the main and ancillary studies. The study procedure and assumptions will be tested during the pilot phase. Ethics and dissemination: The study was approved by the respective ethics committees. An independent Data Safety and Monitoring Board has been established. The findings will be published in peer-reviewed journals and presented at scientific meetings. Trial registration number: NCT02047994